Progress in the application of isothermal amplification technology in the diagnosis of infectious diseases - Bi, Qingshang; Liu, Mengru; Yan, Li; Cheng, Jun; Sun, Qingyang; Dai, Yuzhu; Zou, Lingli (Frontiers in Microbiology, 2025)
Rapid detection of infectious diseases is critical for global public health prevention and control. However, the use of traditional molecular diagnostic methods, including PCR, has been limited because of their cumbersome procedures, complex equipment requirements, operation at different temperatures, and the level of expertise required for operation. Isothermal amplification technology (IAT) provides a rapid, sensitive, specific, simple and less costly method for diagnosing infectious diseases, which has led to revolutionary breakthroughs in molecular diagnostics. This paper summarizes recent progress in IAT technology, which focuses on the principles and applications of core technologies such as NASBA, LAMP, RPA, and RAA. In addition, the combination of IATs with the CRISPR/Cas system, which further revolutionizes nucleic acid detection technology, is explored in this review.